Internal Quality Assurance System Based on Pesantren Values: Towards The Excellence of Schools in Indonesia - Thoyib, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This paper aims to provide an understanding of the internal quality assurance system (SPMI) based on pesantren (Islamic boarding school) values developed by one of the vocational high schools in Indonesia. This research uses a qualitative case-study approach through in-depth interviews, observations, and documentation supported by the interactive analytical model of Miles, Huberman, and Saldana to produce a comprehensive data analysis. The results of the study show that: 1) Determination of quality standards refers to the National Education Standards and Islamic boarding schools' values that are adjusted to the vision, mission, and conditions of the school for further School Self Evaluation to identify strengths, weaknesses, opportunities, threats and appropriate recommendations; 2) Quality fulfillment planning is prepared based on the results of quality mapping in the form of School Work Plans and School Annual Work Plans which contain quality targets, programs, indicators of the success of the person in charge and schedule of activities as well as sources of funding and budget; and 3) The implementation of quality fulfillment is designed by the person in charge of the activity by forming a team for implementing activities, technical activities, and credible budget details to ensure the achievement of the quality implementation that has been declared.